Material Handling and Assembly Process Optimization using Value Stream Mapping - Daniel Derrell Forest; G.H. Massiha (IAES International Journal of Robotics and Automation (IJRA), 2017)
The purpose of this project is to evaluate and optimize an assembly process for ergonomic and productivity considerations. Companies use lean manufacturing as a method for continuous improvement in order to increase throughput and for to reallocate resources for more important tasks. For this project, value stream mapping (VSM) was used to evaluate, analyze, and improve the ergonomic factors of an assembly process and to increasing throughput. With the use of VSM, researchers are able to see the areas of added value, non-added value, and bottlenecks. This project illustrates the implementation of VSM for the minimization of waste, by using the design method to restructure the process of assembly. The results show drastic improvement in assembly time and ergonomic workplace design, while providing a platform for a continuous improvement system.